EKSISTENSI RADIO LOKAL SEBAGAI MEDIA PENDUKUNG PEMILU DI ACEH - Saleh, Rahmat; Khalisni (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
In the past, radio was a tool of struggle that was able to inform news to all corners of Indonesia. Even though this broadcasting tool has become a second alternative due to the impact of the internet, many communities still use it. In Aceh there are radio stations that actively inform election updates and politicians take advantage of this opportunity. This research explains the existence of radio in the implementation of elections both as an educational and campaign media. This study focuses on the role of radio in Aceh in the implementation of elections which ultimately confirms the existence of radio in supporting all stages of the election. The approach used is a case study approach based on field data obtained by researchers. This research involved two local private radio stations and one public radio station, RRI. The research results show that radio has a role as a supporting media for elections by presenting accurate and balanced information so as to reduce hoax issues that have the potential to arise during the election period. Furthermore, radio also acts as a bridge between prospective voters and legislative candidates and political parties. Radio plays a role in strengthening democracy in Aceh. The existence of radio is maintained in the current disruptive era because radio stations in Aceh are converging media from conventional to digital by utilizing technology and digital media platforms. In this way, the existence of radio remains relevant and contributes to providing content that is local, current and useful for the people of Aceh.